In vivo identification of multiple promoter domains of adenovirus EIIA-late promoter. - Bhat, G (1987)
The transcriptional control elements of the Adenovirus (Ad) type 5 EIIA-late (L) promoter were analyzed in the context of the viral chromosome. Promoter mutants constructed in vitro [deletion and linker-scanning (LS)] were re-introduced into the non-essential EIII region of an Ad5 variant which lacked the EIA gene. They were then analyzed in human 293 cells for EIA-dependent and in HeLa cells for EIA-independent transcription. These studies revealed that a minimum of approximately 157 bp upstream from the Cap site are sufficient for the efficient transcription of this promoter in the presence or absence of the EIA gene products. Within the 157-bp sequence, multiple control elements can be identified. These are (i) a sequence block between -55 and -21 which contained a sequence resembling the TATA box and an Sp1 recognition site 5'-TGGGCGTGGT-3', (ii) a sequence block between -84 and -67 which contained a second Sp1 recognition sequence, 5'-CGGGCGGGAT-3' and a 5'-CCAAT-3' box in the non-coding strand and (iii) a 56-bp sequence block between -157 and -101 which contained a 5'-CCAAT-3' sequence in the non-coding strand. The transcriptional pattern of the LS mutants in 293 cells was very similar to that of HeLa cells suggesting that neither of the EIA gene products interact with EIIA-L promoter directly to modulate transcription. A purified Sp1 protein protected DNA sequences from -56 to -33 which includes the Sp1 recognition sequence closer to the cap site whereas the distal Sp1 recognition sequence showed a very weak affinity for the Sp1 factor.(ABSTRACT TRUNCATED AT 250 WORDS)